Formulation and Assessment of Stability Parameters for Acitretin-Loaded NLC Gel - Kapoor, Anupriya (Asian Journal of Pharmaceutics (AJP), 2021)
Purpose: The present investigation intended to develop a lipid-based nanocarrier for topical delivery of acitretin an analog of Vitamin A used in the management of psoriasis by mixing suitable lipids and blends of surfactants and to assess stability parameters for various formulations as per regulatory guidelines. Methods: Nanostructured lipid carriers of acitretin were prepared by the hot homogenization method. Formulations were prepared by varying the concentrations of surfactants (Tween 80 and sodium lauryl sulfate). Prepared formulations were subjected to accelerated stability testing for 6 months the stability samples were evaluated for color, clarity, homogeneity, viscosity, pH, and zeta potential. Results: Higher stability was observed in the F3G formulation. Conclusion: Higher stability in F3G formulation might be attributed to the presence of surfactants in optimum concentration.